2016
DOI: 10.4268/cjcmm20160108
|View full text |Cite
|
Sign up to set email alerts
|

Advanced in studies on anxiolytic effects of natural flavonoids

Abstract: Anxiety is one of the most common diseases endangering human health. Its pathogenesis is complex, the studies on the mechanisms of anxiety disorder are concentrated on neurotransmitter, neuroendocrine, immunologic system. Flavonoids are a kind of compounds which possess a variety of physiological activity, used in plenty of diseases. In recent years, researches of natural flavonoids on anti-anxiety were increasing, but contents were incomplete. It was just involved several neurotransmitters in research area. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In recent years, the anti-anxiety effect of natural flavonoids has attracted many scholars’ attention [ 23 , 24 , 25 , 26 ]. Its anti-anxiety effect may be related to their common structural characteristics: with hydroxyl in the 5,7 positions [ 27 ]. In addition to hesperidin, other bioactive chemical markers are all phenolic acids.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the anti-anxiety effect of natural flavonoids has attracted many scholars’ attention [ 23 , 24 , 25 , 26 ]. Its anti-anxiety effect may be related to their common structural characteristics: with hydroxyl in the 5,7 positions [ 27 ]. In addition to hesperidin, other bioactive chemical markers are all phenolic acids.…”
Section: Discussionmentioning
confidence: 99%
“…The results of numerous studies have confirmed the anxiolytic effect of flavonoids by intracerebroventricular injection in laboratory animals [27][28][29]. For example, the low-dose of flavonoid baicalein (2 μg/rat) has been shown to exert antianxiety effects when injected directly into the central nervous system due to its gabaergic mechanism, which is independent of the benzodiazepine sites.…”
Section: Discussionmentioning
confidence: 84%